2008
DOI: 10.1007/s00246-008-9326-9
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Obesity Associated with High Blood Pressure in Children and Adolescents from João Pessoa, Paraíba, Brazil

Abstract: The objective of this study was to describe the prevalence, correlation, and association of undernutrition and obesity with high blood pressure (HBP). One thousand five hundred seventy (1570) students (808 boys and 762 girls), aged 7-12 years, from João Pessoa, Paraíba (Northeastern Brazil) participated. Measurements of stature, body weight, skinfolds [triceps (TS) and subscapular (SS)], upper-arm circumference (UAC), upper-arm fat area (UAFE), total upper-arm area (TUAA), and BP were taken. Four criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…The rising prevalence of childhood obesity in Brazil is a serious public health dilemma given its established link to chronic health disorders such as dyslipidemia and hypertension [7,15]. Given the regional variance in previous estimates of obesity in Brazilian youth [3-8], it is essential that we monitor the obesity trends in key populations.…”
Section: Discussionmentioning
confidence: 99%
“…The rising prevalence of childhood obesity in Brazil is a serious public health dilemma given its established link to chronic health disorders such as dyslipidemia and hypertension [7,15]. Given the regional variance in previous estimates of obesity in Brazilian youth [3-8], it is essential that we monitor the obesity trends in key populations.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous studies, there were no significant differences in SBP, DBP, and BMI according to sex, ethnicity, and income of the parents. [2125293132] Girls had a significantly lower WC than boys which is probably a biological phenomenon. The relatively small sample in our study may be a reason for not finding significant differences by ethnicity, gender, and income.…”
Section: Discussionmentioning
confidence: 99%
“…[818192024252627282930313233] Some studies have shown that obesity defined as body mass index (BMI) of ≥95 percentile based on gender and age does not correlate well with body fat distribution as compared with waist circumference (WC) which is more accurate in predicting abdominal mass, thus correlating better with hypertension in children. [2434] However, studies have consistently reported that elevated blood pressure (BP), systolic blood pressure (SBP), and diastolic blood pressure (DBP) are significantly correlated with BMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todos os estudos incluídos na revisão dispunham de dados suficientes para compor a meta-análise. 16,17 , e os demais estudos a definiram pela segunda medida 27 , medida alterada 28 ou menor medida 34 . Um estudo não apresentou essa informação.…”
Section: Análise Dos Dadosunclassified